The Queen's Court and Green Mountain manuscripts with other forgeries of the Czech revival - Hanka, Václav (2018)
"The present volume of MSP's Czech Translations Series brings the first scholarly edition in English of the so-called Manuscripts, Czech literary forgeries of the early nineteenth century whose creation and reception represent one of the more remarkable episodes of Romantic forgery. The rich documentation here includes a selection of reviews and polemical articles that the Manuscripts provoked, showing their long term cultural significance and impact, including the central role they played in the development of Czech national consciousness. The annotated translation enables contemporary readers to experience their aesthetic force and perceive the qualities that linked Czech culture to the broad stream of European cultural developments"